Evaluation of the appropriate use of commonly prescribed fluoroquinolones and the risk of dysglycemia - Kabbara WK; Ramadan WH; Rahbany P; Al-Natour S (Dove Medical Press, 2015)
Wissam K Kabbara,1 Wijdan H Ramadan,1 Peggy Rahbany,2 Souhaila Al-Natour3 1Department of Pharmacy Practice, School of Pharmacy, Lebanese American University, Byblos, Lebanon; 2Children’s National Medical Center, Washington, DC, USA; 3Medex Pharmaceutical Company, Beirut, Lebanon Background: Fluoroquinolones are among the most widely prescribed antibiotics. However, concerns about increasing resistant microorganisms and the risk of dysglycemia associated with the use of these agents have emerged.Objective: The primary objective of the study was to evaluate the appropriate use of commonly prescribed fluoroquinolones, including appropriate indication, dose, dose adjustment in renal impairment, and duration of treatment. The secondary objective was to investigate the dysglycemic effect of fluoroquinolone use (hypoglycemia and/or hyperglycemia) in diabetic and nondiabetic patients.Methods: A prospective observational study at a teaching hospital in Lebanon was conducted over a 6-month period. A total of 118 patients receiving broad-spectrum fluoroquinolones (levofloxacin, ciprofloxacin, and moxifloxacin) were identified. Patients were mainly recruited from internal medicine floors and intensive care units.Results: The final percentage for the appropriate indication, dose, and duration of fluoroquinolone therapy was 93.2%, 74.6%, and 57.6%, respectively. A total of 57.1% of the patients did not receive the appropriate dose adjustment according to their level of renal impairment. In addition, dysglycemia occurred in both diabetic and nondiabetic patients. Dysglycemia was more frequently encountered with ciprofloxacin (50.0%), followed by levofloxacin (42.4%) and moxifloxacin (7.6%). Hyperglycemia was more common than hypoglycemia in all groups. The highest incidence of hyperglycemia occurred with levofloxacin (70.0%), followed by ciprofloxacin (39.0%) and moxifloxacin (33.3%). In contrast, hypoglycemia did not occur in the ciprofloxacin group, but it was more common with moxifloxacin (11.1%) and levofloxacin (6.0%).Conclusion: The major clinical interventions for the future will adjust the dose and duration of therapy with commonly prescribed fluoroquinolones. The incidence of hypoglycemia was less common than hyperglycemia. Keywords: fluoroquinolones, ciprofloxacin, levofloxacin, moxifloxacin, dysglycemia